ANALISIS PERSEPSI GURU DAN SISWA DALAM PEMBELAJARAN BIOLOGI PADA PENERAPAN KURIKULUM MERDEKA - Yohana Gulo; Agnes Renostini Harefa; Hardikupatu Gulo; Toroziduhu Waruwu (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT This study aims to analyze teachers’ and students’ perceptions of the implementation of the Merdeka Curriculum in Biology learning and to identify the challenges encountered during the learning process. The study employed a descriptive qualitative approach involving Biology teachers and tenth-grade students at SMA Negeri 1 Moro’o as research subjects. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The results indicate that teachers perceive the Merdeka Curriculum as an educational innovation that provides flexibility in designing learning activities and encourages students to learn according to their interests and potential. Students also demonstrate positive perceptions because Biology learning is considered more engaging, flexible, and student-centered. The challenges faced by teachers include limited instructional time, varying levels of readiness in understanding the new curriculum, and limited resources and access to professional training. Meanwhile, the challenges experienced by students relate to limited learning facilities and laboratory resources. These findings emphasize that the successful implementation of the Merdeka Curriculum in Biology learning is influenced not only by curriculum design but also by teacher readiness, the availability of learning facilities, and a learning environment that supports active student engagement. ABSTRAK Penelitian ini bertujuan menganalisis persepsi guru dan siswa terhadap penerapan Kurikulum Merdeka dalam pembelajaran Biologi serta mengidentifikasi kendala yang dihadapi selama proses pembelajaran. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek guru Biologi dan siswa kelas X di SMA Negeri 1 Moro’o. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru memandang Kurikulum Merdeka sebagai inovasi pembelajaran yang memberikan fleksibilitas dalam merancang kegiatan belajar serta mendorong siswa untuk belajar sesuai minat dan potensi mereka. Siswa juga menunjukkan persepsi positif karena pembelajaran Biologi dinilai lebih menarik, fleksibel, dan berpusat pada siswa. Kendala yang dihadapi guru meliputi keterbatasan waktu, perbedaan tingkat kesiapan dalam memahami kurikulum baru, serta keterbatasan sumber daya dan akses pelatihan. Sementara itu, kendala yang dialami siswa berkaitan dengan keterbatasan fasilitas pembelajaran dan sarana praktikum. Temuan penelitian ini menegaskan bahwa keberhasilan implementasi Kurikulum Merdeka dalam pembelajaran Biologi tidak hanya ditentukan oleh desain kurikulum, tetapi juga oleh kesiapan guru, dukungan fasilitas pembelajaran, serta lingkungan belajar yang mendukung keterlibatan aktif siswa.